Transboundary Water Resources: A Foundation for Regional Stability in Central Asia - Moerlins, John E.; Khankhasayev, Mikhail K.; Leitman, Steven F.; Makhmudov, Ernazar J.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
"Human history becomes more and more a race between education and catastrophe." H. G. Wells Despite a growing awareness of the importance of freshwater, human actions continue to degrade the freshwater ecosystems upon which we depend. Most regions of the world face serious impending problems related to the availability and efficient/equitable distribution of freshwater - these problems become exacerbated when both surface water and groundwater flows between and among multiple countries. As populations grow and the overall demand for water increases, the various and often competing demands for the finite stock of freshwater will increase. These shortages can lead to ecological/resource inefficiencies, economic/industrial problems, degradation of human health, social instability, and even conflict. The Central Asian republics and neighboring countries are currently experiencing these problems - problems that will become exacerbated by global climate change, increasing population and growing demands for water. In response to these growing concerns, on 20-22 June 2006, a NATO-sponsored Advanced Research Workshop (ARW) was organized in Almaty, Kazakhstan entitled, "Facilitating Regional Security in Central Asia through Improved Management of Transboundary Water Basin Resources". This scientific meeting convened leading environmental experts from Central Asia, the Caucasus and from NATO member countries to address the myriad of issues involving shared freshwater among the countries in this region. Issues involving ecology, law, economics, politics, water policy and integrated water management were discussed and evaluated. Against the backdrop of the widely known Aral Sea problem, these leading experts addressed a wide variety of current and emerging issues related to transboundary water management.
Transboundary Water Management Problems in the Central Asia Region -- Problems of Water Resource Management in Central Asia -- Communicating the Issues of the Aral Sea Basin Long-Term Vision or the Aral Sea Basin the Aral Sea Basin Management Model (ASB-MM) -- Water Ecosystems of Central Asia: Important Factors Affecting the Environmental ... Social Prosperity of the Region -- Nato/Ccms Pilot Study Meeting on Transboundary Water Management Issues in the United States & Central Asia: Problem Definition, Regulation and Management -- Management of Transboundary Water Resources in Central Asia and Caucasus Region -- Integrated Management of Transboundary Water Resources in the Aral Sea Basin -- Transition to Iwrm in Lowlands of the Amu Darya and the Syr Darya Rivers -- Improvement of Water Resources Management in the Aral Sea Basin: Subbasin of the Amu Darya River in its Middle Reach -- Integrated Water Resource Management of Transboundary Chu and Talas River Basins -- Chu-Talas Activities -- Mechanisms for Improvement of Transboundary Water Resources Management in Central Asia -- Science for Peace: Monitoring Water Quality and Quantity in the Kura-Araks Basin of the South Caucasus -- Hazardous Pollutant Database for Kura-Araks Water Quality Management -- On Development of GIS-Based Drinking Water Quality Assessment Tool for the Aral Sea Area -- Legal, Technical and Institutional Aspects of Transboundary Water Management -- Lessons Learned from Transboundary Management Efforts in the Apalachicola-Chattahoochee-Flint Basin, USA -- Determining Equitable Utilization of Transboundary Water Resources: Lessons From the United States Supreme Court1 -- Improving Transboundary River Basin Management by Integrating Environmental Flow Considerations -- Transboundary Aquifers as Key Component of Integrated Water Resource Management in Central Asia -- Integrated Water Management.
Keywords: HYDRAULIC ENGINEERING; GEOGRAPHY; ENVIRONMENTAL POLLUTION; GEOSCIENCES; HYDROGEOLOGY; ECONOMIC GEOGRAPHY; WASTE WATER TECHNOLOGY / WATER POLLUTION CONTROL / WATER MANAGEMENT / AQUATIC POLLUTION